Enabling Aqueous Processing of Ni‐Rich Layered Oxide Cathode Materials by Addition of Lithium Sulfate. Issue 2 (14th December 2022) - Heidbüchel, Marcel; Schultz, Thorsten; Placke, Tobias; Winter, Martin; Koch, Norbert; Schmuch, Richard; Gomez‐Martin, Aurora
Abstract: Aqueous processing of Ni‐rich layered oxide cathode materials is a promising approach to simultaneously decrease electrode manufacturing costs, while bringing environmental benefits by substituting the state‐of‐the‐art (often toxic and costly) organic processing solvents. However, an aqueous environment remains challenging due to the high reactivity of Ni‐rich layered oxides towards moisture, leading to lithium leaching and Al current collector corrosion because of the resulting high pH value of the aqueous electrode paste. Herein, a facile method was developed to enable aqueous processing of LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) by the addition of lithium sulfate (Li2 SO4 ) during electrode paste dispersion. The aqueously processed electrodes retained 80 % of their initial capacity after 400 cycles in NCM811||graphite full cells, while electrodes processed without the addition of Li2 SO4 reached 80 % of their capacity after only 200 cycles. Furthermore, with regard to electrochemical performance, aqueously processed electrodes using carbon‐coated Al current collector outperformed reference electrodes based on state‐of‐the‐art production processes involving N ‐methyl‐2‐pyrrolidone as processing solvent and fluorinated binders. The positive impact on cycle life by the addition of Li2 SO4 stemmed from a formed sulfate coating as well as different surface species, protecting the NCM811 surface against degradation. Results reported herein open a new avenue for the processing of Ni‐rich NCM electrodes using more sustainable aqueous routes. Abstract : Keep dry : Ni‐rich layered oxide cathodes are highly promising for high‐energy lithium‐ion batteries, and their aqueous electrode manufacturing is attractive regarding sustainability and recycling aspects. However, aqueous processing of these materials is challenging due to surface reconstruction. Here, it is shown that Li2 SO4 as processing additive can protect the surface against water, leading to improved electrochemical performance.